Functionalizing graphene decorated with phosphorus-nitrogen containing dendrimer for high-performance polymer nanocomposites. (July 2016) - Jin, Yanxian; Huang, Guobo; Han, Deman; Song, Pingan; Tang, Wenyuan; Bao, Jianshe; Li, Rongrong; Liu, Yilin
Abstract: In this paper, we demonstrate a novel strategy for fabricating advanced polymer composites based on functionalized graphene oxide decorated with phosphorus-nitrogen-containing dendrimers (PND-GO). Both X-ray diffraction and transmission electron microscopy results show that reduced PND-GO uniformly disperses within polymer matrix and is exfoliated in polyurethane (PU) via in situ polymerization. Cone calorimetry results show that incorporating 2 wt% reduced PND-GO into PU decreases the peak heat release rate by 53% and prolongs the time to ignition by 28 s as compared with the PU bulk. Besides, the tensile strength and Young's modulus are remarkably enhanced by about 2 times and 5 times, respectively.